Being safe in childbirth : a hermeneutic interpretation of the narratives of women and practitioners : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy, School of Health Sciences, Massey University, New Zealand - Smythe, Elizabeth (Massey University, 1998)
This study uncovers the meaning of 'being safe' related to the experience of childbirth, from the perspectives of practitioners (midwives and doctors), and women. It is informed by the philosophies of Heidegger and Gadamer. Stories and thoughts of the participants are offered to uncover the taken-for-granted nature of the experience of 'being safe' and to expose possible meanings in a new way. The findings of this thesis are that 'being safe' dwells in vulnerability. There are possibilities of unsafely that are beyond human or technological control. There is however a distinctive spirit of practice that promotes safe care. It brings wisdom of learning and experience, alertness to the situation of 'now', and anticipation of problems that might arise. Relationships matter to the provision of safe care. Those that seek mutual understanding and that remain open and dialogical are more likely to anticipate concerns or find problems at their first showing. The setting in which practice is experienced impacts on safety, having the potential to erode or sabotage, to protect or enhance. Any questions asked in hindsight about the meaning of safety need to consider what possibilities, if any, existed for creating safe care, and what other factors influenced the situation to undermine the best intentions of those directly involved. The study concludes by drawing attention to four worldviews which bring conflicting meanings of 'being safe'. The findings of this study show, however, that in the experience of 'being human' there is a common understanding of what it means to be safe in childbirth that reaches beyond the boundaries of worldviews. Where there is a willingness between those involved to find the shared understanding of 'being safe' that overrides the conflicting worldviews, safety is more likely to be achieved. For practitioners, to be safe is a lifetime's struggle. For women, 'being safe' can never be assumed, or taken as a sure promise. 'Being safe' will always be complex, will always be vulnerable, will always be close to danger.
Keywords: Childbirth; Midwifery; Maternal health services; New Zealand; Safety